Ghana Nutrition Improvement Project (GNIP) Establishing sustainable nutrition intervention by “Market base approach with SBCC” through genuinely synergetic PPP - Uesugi, Takashi; Takahashi, Yusuke (2022)
Takashi Uesugi and Yusuke Takahashi Side Event: How Japan’s know-how can help address food and nutrition challenges in the developing world Tokyo Nutrition for Growth (N4G) Summit 2021 NOV 30, 2021